Uncertainty shock from the Brexit vote decreases investment and GDP in the euro area and Germany - Malte Rieth; Claus Michelsen; Michele Piffer (DIW Economic Bulletin, 2016)
The Brexit vote has considerably increased economic uncertainty in Europe and beyond. It will likely affect economic performance and in particular investment in the euro area, which are both already relatively weak. The impact of this uncertainty shock on the euro area and the German economy is estimated with an econometric framework. A counterfactual analysis indicates that the uncertainty associated with the Brexit vote reduces GDP in the model economy for the euro area for more than two years, with a trough of about 0.2 percent after eight months, relative to a situation in which this shock would not have occurred. It also leads to an increase in the unemployment rate and to a mild decline of consumer prices. Investment is estimated to fall by approximately 0.7 percent over the horizon of one year. In Germany, these effects are qualitatively and quantitatively similar. The findings highlight the importance to stimulate investment in the euro area and in Germany, and to minimize uncertainty in the further political process.
Keywords: E32; F15; C32; 330; European Union; United Kingdom; investment; autoregressive models